Preventing CKD in Low- and Middle-Income Countries: A Call for Urgent Action - Oluwatoyin I. Ameh; Udeme E. Ekrikpo; Andre-Pascal Kengne (Kidney International Reports, 2020)
The epidemiologic transition occurring in low- and middle-income countries (LMICs) has led to a surge in chronic kidney disease (CKD) prevalence because of a combination of highly prevalent chronic noncommunicable diseases (NCDs) and communicable diseases (CDs). The progressive rise in CKD prevalence in LMICs threatens the existing weak health systems in these countries as care for advanced CKD remains largely unavailable and unaffordable. An interplay of low literacy levels, poor health-seeking behavior, inadequate health care funding, weak health systems, and lack of skilled nephrology workforce has made it difficult for adequate CKD preventive measures to be implemented. Primary, secondary, and tertiary prevention measures need to be instituted in LMICs by a collaboration of governmental and nongovernmental organizations to stem this tide and help prevent deaths from other NCDs that share similar risk factors with CKD. For these to be effective, locally relevant knowledge is needed to contextualize existing prevention and control solutions, or to develop novel and more appropriate solutions for LMICs. Keywords: CKD, low- and middle-income countries, noncommunicable diseases, prevention